Bonus versus penalty: How robust are the effects of contract framing? - Jonathan de Quidt; Francesco Fallucchi; Felix Kölle; Daniele Nosenzo; Simone Quercia (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We study the relative effectiveness of contracts that are framed either in terms of bonuses or penalties. In one set of treatments subjects know at the time of effort provision whether they have achieved the bonus / avoided the penalty. In another set of treatments subjects only learn the success of their performance at the end of the task. We fail to observe a contract framing effect in either condition: effort provision is statistically indistinguishable under bonus and penalty contracts. We discuss possible reasons for this null result.
Keywords: C9; D03; J24; 330; contract framing; bonus; penalty; fine; loss aversion